Shear behaviour and design of diagonally stiffened stainless steel plate girders. (February 2019) - Yuan, H.X.; Chen, X.W.; Theofanous, M.; Wu, Y.W.; Cao, T.Y.; Du, X.X.
Abstract: The shear behaviour of stainless steel plate girders investigated in this study is related to the introduction of diagonal stiffeners. Four plate girders with or without diagonal stiffeners were fabricated by welding hot-rolled stainless steel plates of different thicknesses. All the plate girders were tested to failure subject to shear loading. The critical shear buckling stress, ultimate resistance and post-peak response were recorded and carefully analysed. Elaborate finite element (FE) models were developed by means of the FE software package ABAQUS and were validated against the test results. A comprehensive parametric analysis of key parameters including the web aspect ratio and slenderness, the flexural stiffness of diagonal stiffeners and the material properties was further conducted, reflecting the influence of these parameters on structural responses. The critical shear buckling stresses obtained from eigenvalue buckling analysis were compared with theoretical predictions of the elastic buckling stress, and a new calculation approach for the shear buckling coefficient of diagonally stiffened web panel that can account for the flexural stiffness of diagonal stiffeners and the effective restraint from flanges was proposed. Based on the obtained ultimate shear resistances, the existing design methods were assessed; and a new design proposal within the framework of EN 1993-1-4 + A1 for predicting the shear resistance of diagonally stiffened stainless steel plate girders was developed. In this novel method, the shear contributions from diagonal stiffeners and the shear buckling coefficients for diagonally stiffened web panels were revised. The reliability of the new proposal was also confirmed by further statistical analysis. Highlights: Tests on diagonally stiffened stainless steel plate girders in shear for the first time. Diagonal stiffeners increase the critical shear buckling stress and the shear resistance considerably. Novel method for calculating the shear buckling coefficient of diagonally stiffened web is proposed. New design approach for predicting the ultimate shear resistance is proposed. Statistical analysis verifies the reliability of the proposed method.